PELUANG DAN TANTANGAN LEMBAGA KEUANGAN SYARIAH MENGHADAPI MEA (MASYARAKAT EKONOMI ASEAN) - Dedi Irawan (Jurnal Signaling, 2022)
This study aims to determine the opportunities and challenges of Islamic financial institutions in facing the ASEAN Economic Community (AEC) and how the strategies of Islamic Financial Institutions to win the competition of the ASEAN Economic Community (AEC). The method used is a qualitative method with a descriptive analysis approach that seeks to analyze various challenges, opportunities and strategies of Islamic Financial Institutions in facing the AEC (Asian Economic Community). The results of the study indicate that the opportunities for Islamic financial institutions in Indonesia can be strong in the face of the MEA. The challenges for Islamic financial institutions in Indonesia are the low quality and quantity of human resources with a sharia economic background, the sharia financial market share which is still relatively small compared to conventional finance, the level of understanding and awareness of sharia society is still lacking in the economy, lack of product development innovation and services that are competitive and based on community needs. Lack of support from the government, both in the form of regulatory support and government capital support. Strategies that must be carried out by LKS in Indonesia to increase competitiveness so that they are able to survive in the MEA competition are: Improving the quality and quantity of human resources, socialization and education to the community, service improvement and product differentiation, and support from all stakeholders, especially the government.